(3GdaSQ aj TQM OjhGf GdeJfHjs - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s ((3fGSN KGf(B/ (3bhGe GdaGQGHj GdCJbGfj SfI (B736 (3g```` s)
(3ChdgG (B:s
(3HbjI MQa GdOGd(B: (3cGf bhe aj UHGg bO hThG Hg Edi GdSdWGf hJcPHhG Ydjg hbGdhG dg bO GfbGO dg Ndb cKjQ ef GdYQH s
(3BNQgG (B:s
(3CjfaY aj GdNjeI GdoYRd hTed ef RgQgG jTed s
(3cJHgG fGSNGfs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B652s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B87 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B810s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs